(untitled) - Collier, John G. (Cambridge, U.K., 2001)
This clear and authoritative introduction to the principles of private international law, a complex and rapidly changing area, now appears in a revised and fully updated form. In this new third edition, the chapters on tort, jurisdiction, and staying of actions have been almost entirely rewritten. The chapter on the Brussels and Lugano Conventions has been recast and expanded. The growing influence of European Union law on U.K. private international law is evident in this new edition, which will be a valuable text for students and practitioners alike.
Keywords: Conflict of laws,Mâu thuẫn giữa các luật; Great Britain,Anh quốc